2021
DOI: 10.1002/jctb.6751
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐modifying enzymes: a green and environmental responsive technology for organic compound degradation

Abstract: The applications of enzymes have reached an increasing prominence in the scenario of biocatalysis, stimulated mainly by advances in biotechnological processes to obtain products of high added value. The justification for this is the relevant growth of industrial activities that promote the production of various organic contaminants. Thus, enzymes offer the potential to improve industrial processes used in the food, pharmaceutical, textile, pulp and paper sectors. Specifically, the lignin‐modifying enzymes (LME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 146 publications
0
15
0
Order By: Relevance
“…However, still, there are some other microbes with specific properties, which can degrade or decompose the KL more efficiently, which need to be identified and explored in detail. Laccase, LiP, and MnP are major ligninolytic enzymes, which have attracted more attention in the recent decade for the decay/breakdown of lignocellulosic waste and their derivatives [7] . Furthermore, laccase is a copper-containing enzyme while LiP and MnP are heme-containing enzymes produced by various microorganisms that retain the potential to degrade KL [24] .…”
Section: Introductionmentioning
confidence: 99%
“…However, still, there are some other microbes with specific properties, which can degrade or decompose the KL more efficiently, which need to be identified and explored in detail. Laccase, LiP, and MnP are major ligninolytic enzymes, which have attracted more attention in the recent decade for the decay/breakdown of lignocellulosic waste and their derivatives [7] . Furthermore, laccase is a copper-containing enzyme while LiP and MnP are heme-containing enzymes produced by various microorganisms that retain the potential to degrade KL [24] .…”
Section: Introductionmentioning
confidence: 99%
“…WRFs play an essential role in the environment because they have the capacity to process the three components of lignocellulosic biomass (cellulose, hemicellulose and lignin) [ 3 ]. These fungi can use lignin as the only source of carbon and energy and mineralize it to CO 2 [ 28 ]. This action is due to the LMEs that they produce, such as lignin peroxidase, manganese peroxidase and laccase [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the genes that encode laccases can be positively regulated by factors such as the carbon/nitrogen ratio in the culture or induced by byproduct components (citrus washing pulp) at specific pH and rpm as demonstrated in P . sajor-caju [ 28 ]. Metal ions also influence the expression of laccases during culture [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phanerochaete chrysosporium is known to degrade lignin and various aromatic pollutants during secondary metabolism in the stationary phase. Peroxidases (manganese peroxidase and lignin peroxidase) and the extracellular H 2 O 2 -producing enzyme system of oxidase produced by these organisms are the main enzymes involved in the metabolism of lignin degradation, synthesized in response to the limited levels of nitrogen, carbon, and sulfur; also adopted various metabolic strategies to degrade complex polymeric substrates [1][2][3][4][5]. Many studies have shown that the type of strain and medium culture conditions affected the type of isoenzyme of LiP produced.…”
Section: ■ Introductionmentioning
confidence: 99%